2013
DOI: 10.1037/a0032656
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of attention and pathological gambling.

Abstract: In the study of addiction, attentional bias refers to the observation that substance-related cues tend to capture the attention of experienced substance users. Attentional bias is a cognitive intermediate in the conditioned association between drug-related cues, craving, and relapse. Numerous studies have documented the existence of attentional bias for cues associated with substances. By contrast, few studies have investigated attentional bias in individuals with pathological gambling (PG) or problematic gamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
6
20
3
Order By: Relevance
“…Our finding that high-risk gamblers exhibit gambling-specific attentional biases corroborates previous work (Boyer & Dickerson, 2003;McCusker & Gettings, 1997;Vizcaino et al, 2013). In addition, it builds on prior work by pinpointing the attentional component involved in these biases (i.e., sustained attention rather than initial orienting) and by measuring the extent of these biases relative to established emotional distractors.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our finding that high-risk gamblers exhibit gambling-specific attentional biases corroborates previous work (Boyer & Dickerson, 2003;McCusker & Gettings, 1997;Vizcaino et al, 2013). In addition, it builds on prior work by pinpointing the attentional component involved in these biases (i.e., sustained attention rather than initial orienting) and by measuring the extent of these biases relative to established emotional distractors.…”
Section: Discussionsupporting
confidence: 77%
“…It makes sense that clinically meaningful biases be tied to later stages of processing, as earlier attentional biases are more fleeting and may have less enduring consequences. However, unlike the case in previous work (Baron et al, 1995;McCusker & Gettings, 1997;Molde et al, 2010;Vizcaino et al, 2013), there was some evidence of a (nonspecific) gambling bias, analogous to biases for negative distractors, in our low-risk gambler group. One reason we detected such a bias, where others have not, may be that we included both non-problem and low-risk gamblers as our control group, whereas others have used non-gamblers, non-problem gamblers, or a mixture of both (Baron et al, 1995;Brevers, Cleeremans, Tibboel et al, 2011;McCusker & Gettings, 1997;Molde et al, 2010;Vizcaino et al, 2013).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…To date, the majority of the studies evaluating attentional biases have employed the addiction Stroop Task that is unanimously considered a measure of the early stages of cognitive processing (Cox et al, 2006). Other studies (e.g., Grant and Bowling, 2015;Vizcaino et al, 2013) found no bias in attentional engagement and demonstrated that gambling frequency is associated with the maintenance of attention when using gambling-related stimuli. A recent study (Brevers et al, 2011b) used an attentional paradigm that allows the evaluation of these two attentional components.…”
Section: Introductionmentioning
confidence: 99%